Konsep Pendidikan Islami dalam Tafsir Tarbawi: Kajian Tematik Ayat-Ayat Tentang Pembentukan Karakter - Mustain, Mustain (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2025)
This study aims to examine the concept of Islamic education in tarbawi tafsir, especially in the formation of student character through thematic studies of Qur'anic verses. Student character building is an important aspect of education that needs to be integrated with religious values contained in the Qur'an. This research uses a qualitative approach with a type of literature study research (library research), which focuses on analysing relevant tafsir and Qur'anic verses related to education and character. The main data sources in this research are tafsirs that have been recognised for their credibility in the academic world, and secondary sources in the form of articles, books, and previous research related to tarbawi tafsir and character education. The purpose of this study is to explore how tafsir tarbawi can be applied in Islamic education in order to form strong student characters, noble character, and in accordance with Islamic teachings. The results show that tafsir tarbawi has an important role in character education, by integrating moral values from Qur'anic verses that can be applied in students' daily lives. Although tarbawi tafsir has great potential, its implementation in formal education still faces challenges, which require more efforts in integrating this tafsir in the Islamic education curriculum in schools.